Pedotransfer functions to assess adsorbed phosphate using iron oxide content and magnetic susceptibility in an Oxisol - Camargo, L. A. [UNESP]; Marques, J. [UNESP]; Pereira, G. T. [UNESP]; Alleoni, L. R. F.; Bahia, A. S. R. de S. [UNESP]; Teixeira, D. De B. [UNESP] (Wiley-Blackwell, 2016)
Adsorbed phosphate in soils can be chemically extracted; however, this process is both time-consuming and not cost-effective if large numbers of samples have to be analysed. Indirect assessment of adsorbed phosphate by pedotransfer functions (PTFs) can help optimize fertilizer strategies. This study aimed to evaluate the spatial variability of adsorbed phosphate (P-ads), iron oxides and magnetic susceptibility (MS) in oxisols and to calibrate PTFs to predict P-ads. A total of 308 soil samples were collected from Hapludox and Eutrudox soils formed from sandstone in Brazil. The contents of clay (196-607 g/kg), iron oxides (40-165 g/kg), MS (1.2-29 x 10(-6) m(3)/kg) and P-ads (327-842 mg/kg) were in the range of typical values for these highly weathered soils. This study showed that the attributes studied were spatially dependent. Geomorphic surfaces enabled understanding of spatial variability and helped to develop a more efficient sampling scheme to calibrate PTFs. Moreover, the adsorbed phosphate in these oxisols could be predicted by a PTF using iron oxides and MS as predictors. The MS attribute enabled the most accurate prediction (concordance coefficient = 0.95, root-mean-square error = 46 mg/kg and relative improvement in root-mean-square error = -4.12) of spatial variability through PTF compared to other predictors.
Keywords: Diffuse reflectance spectroscopy; X-ray diffraction clay; geostatistics; goethite; hematite